Поиски новых возможностей комплексной коррекции аутизма - Cherevko, N. A.; Novikov, P. S.; Arkhipov, A. M.; Vekovtsev, A. A.; Bylin, P. G.; Bychina, A. A.; Artemyeva, A. D. (Патогенез, 2022)
Тезисы конференции